2021
DOI: 10.1038/s41598-021-95170-9
|View full text |Cite
|
Sign up to set email alerts
|

A deep-learning method using computed tomography scout images for estimating patient body weight

Abstract: Body weight is an indispensable parameter for determination of contrast medium dose, appropriate drug dosing, or management of radiation dose. However, we cannot always determine the accurate patient body weight at the time of computed tomography (CT) scanning, especially in emergency care. Time-efficient methods to estimate body weight with high accuracy before diagnostic CT scans currently do not exist. In this study, on the basis of 1831 chest and 519 abdominal CT scout images with the corresponding body we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…This approach showed a strong correlation (r = 0.969) between the measured and predicted body weights, but it is limited to polytrauma patients who undergo whole-body CT scans. Recently, body-weight prediction using deep learning from chest CT scout images showed an MAE of 2.75 kg and a strong correlation (ρ = 0.947) between the actual and predicted body weights; however, the overweight cases tended to be underestimated because of the limited number of training sets [9].…”
Section: Gascho Et Al Developed a Linear Regression Equation Based On...mentioning
confidence: 99%
See 2 more Smart Citations
“…This approach showed a strong correlation (r = 0.969) between the measured and predicted body weights, but it is limited to polytrauma patients who undergo whole-body CT scans. Recently, body-weight prediction using deep learning from chest CT scout images showed an MAE of 2.75 kg and a strong correlation (ρ = 0.947) between the actual and predicted body weights; however, the overweight cases tended to be underestimated because of the limited number of training sets [9].…”
Section: Gascho Et Al Developed a Linear Regression Equation Based On...mentioning
confidence: 99%
“…The arti cial intelligence (AI)-based approach has shown many encouraging results in medical imaging analysis. Particularly, a convolutional neural network (CNN) can achieve excellent predictions [9][10][11][12]. The use of CNN to predict body weight from chest and abdominal CT scout images has also been shown [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before performing a typical CT scan, 2D scout views, also konwn as topograms or planning radiographs, are initially obtained for prescribing CT slices and modulating x-ray tube current for dose reduction. Radiologists have found that planning radiogaphs carry significant diagnostic information (1)(2)(3)(4), although they have limited information compared to radiography and CT. These X-ray imaging modes have their strengths and weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Bodyweight fluctuations are important indications for a range of medical disorders, and in some cases, such as congestive heart failure, they are key determinants of intensive care measures [ 1 ]. Many doctors and medical professionals require patient weight for various diagnostic procedures and prescription of medication or diet [ 2 ]. Bodyweight, as well as weight change, is particularly important for critically sick patients hospitalized in intensive care units (ICUs), since it is a direct measure of fluid balance effectiveness and general health.…”
Section: Introductionmentioning
confidence: 99%